Nano-Synthesized Silver Particles and Azolla Pinnata Extract Larvicidal Effects Against Aedes Aegypti (Diptera: Culicidae) - R. Ravi, I. H. Ishak, M.F. Mohd Amin, M. S. M. Rasat, M.A. Salam, M.A. Mohd Amin (International Journal of Advanced Science and Technology, 2020)
Dengue is a worldwide issue which is mostly found in tropical and sub-tropical climates around the world. Human being can get infected with dengue through the bite of female mosquito of Aedes aegypti. The widely used synthetic insecticide in the operation of mosquito control could result in unfavorable impacts to the environment, human health and non-target organism. Considering these issues, environmentally friendly insecticides from plant extract have been used as green alternatives by recent researchers. Unfortunately, the method of using plant extract as insecticide requires a large amount of raw plants to be used. In relation to this problem, the use of nanoparticles that possesses unique characteristics including small size and potential in changing physical, chemical and biological properties of organisms were studied. Nano-synthesized silver particles from Azolla pinnata extract were thus investigated in this study in order to determine its efficacy as Aedes aegypti larvicide. Nano-synthesized silver particles from Azolla pinnata extract were prepared in six different concentrations and set in plastic cups. Late third instar larvae of Aedes aegypti were being used in all tests. Based on the findings of the experiment, there was no mortality of larvae recorded in control groups after 24 hours of exposure. The lowest mortality recorded was at 10 ppm with only 7.5% mortality, while 95% mortality was recorded for the highest concentration which was 250 ppm. Meanwhile, the LC50 and LC95 obtained at 95% confidence interval after 24 hours of exposure were 121.570 ppm and 369.438 ppm respectively. Further studies should be done to determine the mechanisms of silver nanoparticles in aiding Azolla pinnata as an effective larvicide in the future.